Kepuasan Belanja Fashion Online dan Offline (Studi pada Muslimah Kecamatan Selebar Kota Bengkulu Provinsi Bengkulu) - Nurhasanah Fitri Ayu; Yulina Agata; Mepin Satriani; Asnaini Asnaini; Debby Arisandi (Ekonomis: Journal of Economics and Business, 2022)
The purpose of this study is 1) to determine the effect of product quality, price, service quality, emotional factors, cost and convenience on fashion online and offline. 2) to compare fashion online and offline. This type of research is comparative associative with a quantitative approach. The research subjects were 130 women aged 20-40 years in Selebar District, Bengkulu City.was a Purposive sampling technique used to take samples. Data analysis used multiple linear regression and dependent t-test. The results showed that there was a simultaneous influence of product quality, price, service quality, emotional factors, cost and convenience on fashion online and offline. From the results of the equation product quality, price, cost and convenience affect offline, service quality and emotional factors have no effect offline. Meanwhile, from the results of the equation product quality, price, and service quality do not affect online fashion, emotional factors, cost and convenience influence online fashion. The results of this study also mention that there is a difference between fashion online and offline